Dynamic Cerebral Autoregulation Following Acute Ischaemic Stroke: Comparison of Transcranial Doppler and Magnetic Resonance Imaging Techniques - Jara-Valencia, J (Nature Publishing Group, 2016)
Novel MRI-based dynamic cerebral autoregulation (dCA) assessment enables the estimation of both global and spatially discriminated autoregulation index values. Before exploring this technique for the evaluation of focal dCA in acute ischaemic stroke (AIS) patients, it is necessary to compare global dCA estimates made using both TCD and MRI. Both techniques were used to study 11 AIS patients within 48 h of symptom onset, and nine healthy controls. dCA was assessed by the rate of return of CBFV (R turn) following a sudden drop induced by the thigh cuff manoeuvre. No significant between-hemisphere differences were seen in controls using either the TCD or MRI technique. Inter-hemisphere averaged R turn values were not different between TCD (1.89 ± 0.67%/s) and MRI (2.07 ± 0.60%/s) either. In patients, there were no differences between the affected and unaffected hemispheres whether assessed by TCD (R turn 0.67 ± 0.72 vs. 0.98 ± 1.09%/s) or MRI (0.55 ± 1.51 vs. 1.63 ± 0.63%/s). R turn for both TCD and MRI was impaired in AIS patients compared to controls in both unaffected and affected hemispheres (ANOVA, p = 0.00005). These findings pave the way for wider use of MRI for dCA assessment in health and disease. © The Author(s) 2015.